A low-temperature sintered dense bulk ceramic material and preparation method thereof

By mixing inorganic ceramic powder with precursor solution/powder and sintering at low temperature, the problem of gas influence in the preparation of dense bulk ceramic materials at low temperature was solved, and the preparation of high-density and high-strength ceramic materials with good oxidation resistance was achieved.

CN116947490BActive Publication Date: 2025-01-28HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310946144.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-01-28
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

In existing technologies, when preparing large, dense bulk ceramic materials at low temperatures, the large amount of gas generated by the decomposition of precursors affects the quality of the ceramics, making it difficult to achieve high density and high strength in ceramic materials.

Method used

Dense bulk ceramic materials are prepared by mixing inorganic ceramic powder with a small amount of precursor solution/powder and sintering at low temperature. During the sintering process, the precursor decomposes to generate an inorganic amorphous ceramic phase, which uniformly coats and fills the surface and voids of the inorganic ceramic powder, providing a driving force to promote the rearrangement of the inorganic ceramic powder.

Benefits of technology

This method achieves high density and high strength in ceramic materials, improves oxidation resistance, avoids the reduction in activity caused by high-temperature pyrolysis of precursors, and simplifies the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116947490B_ABST
    Figure CN116947490B_ABST
Patent Text Reader

Abstract

The present invention provides a low-temperature sintered dense bulk ceramic material and a preparation method thereof, and relates to the technical field of ceramic materials. The preparation method includes using an inorganic ceramic powder and a precursor solution / powder as raw materials, and after mixing and dispersing, a mixed powder is obtained, wherein the weight percentage of the precursor solution / powder in the mixed powder is 10-40wt%; the mixed powder is subjected to low-temperature sintering under a protective atmosphere to obtain a low-temperature sintered dense bulk ceramic material. In the present invention, the precursor solution / powder is cracked at high temperature to generate an inorganic amorphous ceramic phase, which is uniformly coated and filled on the surface and gaps of the original inorganic ceramic powder. During the sintering process, these inorganic amorphous ceramic network structures provide a driving force for the rearrangement of the original inorganic ceramic powder particles, thereby realizing the low-temperature sintering and densification of the inorganic ceramic powder to obtain a dense bulk ceramic material. The bulk ceramic material prepared by the present invention has high density, high strength and good antioxidant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic materials, and in particular to a low-temperature sintered dense block ceramic material and a preparation method thereof. Background Art

[0002] Ceramic materials are widely used in structural materials and functional materials due to their excellent properties such as high hardness, high strength and high chemical stability. However, due to the strong covalent bond in ceramic materials, there are problems such as difficulty in sintering, especially the preparation of large pieces of dense bulk ceramics at low temperature, which limits the application field of ceramic materials to a certain extent. Polymer conversion ceramic technology is generally used in the prior art to prepare ceramic materials at a lower temperature. However, polymer conversion ceramic technology is a technology that obtains inorganic or nano ceramic materials by cross-linking, curing, high-temperature cracking, sintering and other processes of organic precursors. The polymer precursor will produce a large amount of gas during the cross-linking cracking process. During the ceramicization process, due to volume shrinkage, a large number of holes and microcracks will appear in the prepared ceramics, thereby reducing the quality of the ceramics. In order to solve the problem of affecting the quality of ceramics due to the release of a large amount of gas due to the cracking of the precursor, the prior art also chooses to add fillers to the precursor, but the dispersion of the filler has higher requirements. Summary of the invention

[0003] The problem to be solved by the present invention is how to prepare high-density and high-strength bulk ceramic materials by low-temperature sintering. The existing technology using polymer-to-ceramic technology has the problem of affecting the quality of ceramics due to the generation of a large amount of gas due to the cracking of the precursor.

[0004] In order to solve the above problems, the present invention provides a method for preparing a low-temperature sintered dense bulk ceramic material, comprising:

[0005] Inorganic ceramic powder and precursor solution / powder are used as raw materials, and mixed and dispersed to obtain a mixed powder, wherein the weight percentage of the precursor solution / powder in the mixed powder is 10-40wt%;

[0006] The mixed powder is sintered at low temperature under a protective atmosphere to obtain a low-temperature sintered dense bulk ceramic material.

[0007] Preferably, the precursor solution / powder is a precursor solution or a precursor powder, the precursor solution includes one or more of polysilane, polysilazane, polycarbosilane, polysiloxane, polyborazane and polyborosilazane, and the precursor powder includes one or more of polysilane, polysilazane, polycarbosilane, polysiloxane, polyborazane and polyborosilazane.

[0008] Preferably, the inorganic ceramic powder and the precursor solution / powder are used as raw materials, and after mixing and dispersing, the mixed powder is prepared, which comprises:

[0009] Uniformly dispersing the inorganic ceramic powder and the precursor solution in a solvent to obtain a mixed solution;

[0010] heating and stirring the mixed solution to evaporate the solvent until the mixed solution becomes a paste;

[0011] The mixed solution in a paste state is dried, solidified, and crushed to obtain the mixed powder.

[0012] Preferably, the heating and stirring of the mixed solution to evaporate the solvent until the mixed solution becomes a paste comprises:

[0013] The mixed solution was placed on a magnetic stirrer, and the solvent was evaporated at 50-55° C. until the mixed solution became a paste.

[0014] Preferably, the drying and curing of the paste-like mixed solution comprises:

[0015] The paste-like mixed solution is first dried at 80-90° C. for 4-5 hours to fully remove the solvent, and then heated to 170-180° C. and cured for 4-6 hours.

[0016] Preferably, the inorganic ceramic powder and the precursor solution / powder are used as raw materials, and after mixing and dispersing, the mixed powder is prepared, which comprises:

[0017] The precursor powder is solidified under a protective atmosphere to obtain a precursor block;

[0018] The precursor block is crushed to obtain precursor powder, and the precursor powder and the inorganic ceramic powder are ball-milled to obtain the mixed powder; or the precursor block and the inorganic ceramic powder are mixed and crushed to obtain the mixed powder.

[0019] Preferably, the step of uniformly dispersing the inorganic ceramic powder and the precursor solution in a solvent to obtain a mixed solution comprises:

[0020] The precursor solution is dissolved in the solvent, and ultrasonic stirring is performed for 10-15 minutes. The inorganic ceramic powder is added, and ultrasonic stirring is continued for 20-30 minutes to obtain the mixed solution.

[0021] Preferably, the low temperature sintering includes spark plasma sintering, and the heating rate during the spark plasma sintering is 50-150° C. / min, the sintering temperature is 1500-1700° C., the applied pressure is 40-50 MPa, and the holding time is 3-10 min.

[0022] Preferably, the low-temperature sintering includes hot pressing sintering, and the heating rate during the hot pressing sintering is 5-30°C / min, the sintering temperature is 1500-1700°C, the axial pressure is 50-60MPa, and the holding time is 30-120min.

[0023] The advantages of the method for preparing a low-temperature sintered dense bulk ceramic material of the present invention compared with the prior art are:

[0024] The present invention uses inorganic ceramic powder as raw material, adds a small amount of precursor solution or powder to the inorganic ceramic powder, and obtains a mixed powder after mixing and dispersing, and then the mixed powder is sintered at low temperature under a protective atmosphere to obtain a dense bulk ceramic material. During the low-temperature sintering process, the precursor solution or powder acts as a sintering aid, and is cracked to generate an inorganic amorphous ceramic phase, which is uniformly coated and filled on the surface and gaps of the original inorganic ceramic powder. During the sintering process, the inorganic amorphous ceramic phase network structure generated by the cracking of the precursor solution or powder provides a driving force for the rearrangement of the original inorganic ceramic powder particles, thereby realizing the low-temperature sintering densification of the inorganic ceramic powder to obtain a dense bulk ceramic material. The present invention promotes the sintering of the inorganic ceramic powder by a small amount of precursor phase, and the prepared bulk ceramic material has a higher density, higher strength and good antioxidant properties.

[0025] The present invention also provides a low-temperature sintered dense bulk ceramic material, which is prepared based on the preparation method of the low-temperature sintered dense bulk ceramic material.

[0026] The advantages of the low-temperature sintered dense block ceramic material of the present invention over the prior art are:

[0027] The dense bulk ceramic material comprises a precursor-derived ceramic phase and an original inorganic ceramic phase; the derived ceramic phase is obtained by pyrolysis of the precursor at high temperature; the precursor-derived ceramic phase uniformly covers and fills the surface and voids of the inorganic ceramic phase. The advantages of the ceramic material and the preparation method of the present invention are the same as those of the prior art, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a flow chart of a method for preparing a low-temperature sintered dense bulk ceramic material according to an embodiment of the present invention;

[0029] Figure 2 The fracture microscopic morphology of the ceramic materials prepared in Example 1 of the present invention and the comparative example. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0031] A method for preparing a low-temperature sintered dense bulk ceramic material according to an embodiment of the present invention comprises:

[0032] Inorganic ceramic powder and precursor solution / powder are used as raw materials, and mixed and dispersed to obtain a mixed powder, wherein the weight percentage of the precursor solution / powder in the mixed powder is 10-40wt%;

[0033] The mixed powder is sintered at low temperature under a protective atmosphere to obtain a low-temperature sintered dense bulk ceramic material.

[0034] Ceramic materials have high strength and stability due to the strong covalent bonds in them, but they are also difficult to sinter and finish, which limits their application areas. Polymer-to-ceramic is a technology that converts silicon-based polymer precursors into ceramics through cross-linking, high-temperature cracking, and crystallization. It has the advantages of low energy consumption and good processing and forming properties. Therefore, polymer-to-ceramic technology is widely used in the prior art to convert polymer precursors into ceramics. However, at the same time, this technology also has many defects. For example, it requires the precursor to be cracked at high temperature before mixing with inorganic ceramics for sintering. Since the precursor has been cracked into inorganic ceramic powder during the high-temperature cracking process, its activity is reduced during the subsequent sintering process, and the large amount of gases such as hydrogen and helium generated during the cracking process will also affect the sintering quality of the ceramic.

[0035] The embodiment of the present invention provides a method for preparing a dense bulk ceramic material by solid phase reaction sintering, which uses inorganic ceramic powder as the main phase and precursor solution / powder as a sintering aid, and sintering is performed after mixing and dispersing. By adding a small amount of precursor solution / powder, the purpose of promoting the sintering of inorganic ceramic powder is achieved, and a bulk ceramic material with high density and high strength is prepared. Among them, the precursor solution / powder represents a precursor solution or a precursor powder. When the precursor solution is used as the raw material, the inorganic ceramic powder and the precursor solution are a solid-liquid mixture. The inorganic ceramic powder cannot be plastically deformed, and the precursor solution is a liquid. Therefore, after adding the precursor solution, the flow and diffusion of the inorganic ceramic powder can be accelerated, so that it produces plastic flow, which is similar to adding water to the particles, and the water can drive the particles to flow. When the precursor powder is used as the raw material, the inorganic ceramic powder and the precursor powder are solid-solid mixed. This method is a mixture between particles. Compared with the solid-liquid mixture, the liquid is coated on the powder surface, and the mixing effect is slightly worse, but it can also promote sintering. Therefore, when the inorganic ceramic powder is mixed with the precursor solution / powder, during the sintering process, the precursor is cracked to generate an inorganic amorphous ceramic phase, which is uniformly coated and filled on the surface and gaps of the inorganic ceramic powder. These inorganic amorphous ceramic network structures provide a driving force for the rearrangement of the inorganic ceramic powder particles, so that the inorganic ceramic powder can be sintered and densified at low temperature, thereby obtaining a dense bulk ceramic material. Thus, by uniformly coating the inorganic powder with the precursor, the sintering activity of the precursor will not be lost. Compared with the mono- or poly-oxide ceramics used in the prior art as sintering aids, the present embodiment is very conducive to sintering and improving the density and purity of the product, without the need for cumbersome purification treatment.

[0036] Compared with the polymer conversion ceramic technology in the prior art that requires the precursor to be subjected to high-temperature pyrolysis treatment, the precursor solution / powder of this embodiment does not need to be subjected to high-temperature pyrolysis in advance to reduce its sintering activity. Instead, it is used as a sintering aid and is fully mixed with the inorganic ceramic powder before sintering together. During the sintering process, the precursor is cracked into an amorphous network structure, which is evenly coated on the surface of the inorganic ceramic powder or filled in the gaps of the inorganic ceramic powder. These amorphous network structures can provide a driving force for the movement of the original inorganic ceramic powder and rearrange the inorganic ceramic powder particles, so that the prepared ceramic material has a higher density. At the same time, since the precursor retains a higher sintering activity, the prepared ceramic material also has higher strength and good antioxidant properties.

[0037] In some embodiments, the inorganic ceramic powder includes inorganic SiBCN ceramic powder, inorganic BN ceramic powder, inorganic Si3N4 ceramic powder, inorganic SiC ceramic powder, inorganic BC4 ceramic powder, etc. The method of this embodiment is applicable to ceramic powders with strong covalent bonds that are difficult to sinter.

[0038] The precursor solution / powder is a precursor solution or a precursor powder, the precursor solution includes one or more of polysilane, polysilazane, polycarbosilane, polysiloxane, polyborazane and polyborosilazane, and the precursor powder includes one or more of polysilane, polysilazane, polycarbosilane, polysiloxane, polyborazane and polyborosilazane.

[0039] In some embodiments, the inorganic ceramic powder and the precursor solution / powder are used as raw materials, and after mixing and dispersing, the mixed powder is prepared, which comprises:

[0040] Uniformly dispersing the inorganic ceramic powder and the precursor solution in a solvent to obtain a mixed solution;

[0041] heating and stirring the mixed solution to evaporate the solvent until the mixed solution becomes a paste;

[0042] The mixed solution in a paste state is dried, solidified, and crushed to obtain the mixed powder.

[0043] In this embodiment, when a precursor solution is used as an additive, a solid-liquid mixing method is used to mix the inorganic ceramic powder with the precursor solution to obtain a mixed solution, and then the mixed solution is heated under stirring conditions to evaporate the solvent. Under stirring conditions, the inorganic ceramic powder and the precursor solution can be ensured to be uniformly dispersed. After evaporating the solvent until the solution becomes a paste, the paste solution is dried to fully remove the solvent, and then a block precursor is obtained by curing, and the mixed powder is obtained after crushing. Through this mixing method, the inorganic ceramic powder and the precursor solution can be uniformly dispersed, so that the precursor can be uniformly coated or filled on the surface or gap of the inorganic ceramic powder, and the driving force is provided for the rearrangement of the inorganic ceramic powder particles in the subsequent sintering process, so that the inorganic amorphous ceramic phase produced by the cracking of the precursor is uniformly and densely combined with the original inorganic ceramic powder.

[0044] Since the precursor solution is liquid, it is generally cross-linked and cured in the prior art, and becomes a block after curing, which is crushed into powder, and the cured product is first cracked at high temperature. In the scheme of this embodiment, the precursor is neither cured nor cracked, but the liquid precursor is directly mixed with the inorganic ceramic powder, which can achieve uniform coating of the inorganic ceramic powder by the precursor without losing the sintering activity of the precursor, because if the precursor is cracked first, it is equivalent to ceramic powder after cracking, and it cannot promote sintering in the subsequent sintering process or the promotion effect is not obvious.

[0045] In some embodiments, the heating and stirring of the mixed solution to evaporate the solvent until the mixed solution becomes a paste comprises:

[0046] The mixed solution was placed on a magnetic stirrer, and the solvent was evaporated at 50-55° C. until the mixed solution became a paste.

[0047] In this embodiment, a magnetic stirrer is used to magnetically stir the mixed solution so that the mixed solution is in a uniformly dispersed state, so that during the evaporation of the solvent, the inorganic ceramic powder and the precursor are uniformly distributed.

[0048] In some embodiments, the drying and curing of the paste-like mixed solution includes:

[0049] The paste-like mixed solution is first dried at 80-90° C. for 4-5 hours to fully remove the solvent, and then heated to 170-180° C. and cured for 4-6 hours.

[0050] Exemplarily, the paste-like mixed solution is transferred to a vacuum drying oven to remove the solvent, and then the temperature is increased to perform vacuum curing treatment.

[0051] In some embodiments, the inorganic ceramic powder and the precursor solution / powder are used as raw materials, and after mixing and dispersing, the mixed powder is prepared, which comprises:

[0052] The precursor powder is solidified under a protective atmosphere to obtain a precursor block;

[0053] The precursor block is crushed to obtain precursor powder, and the precursor powder and the inorganic ceramic powder are ball-milled to obtain the mixed powder; or the precursor block and the inorganic ceramic powder are mixed and crushed to obtain the mixed powder.

[0054] In this embodiment, when the precursor powder is used as an additive, the precursor is first solidified into a block, and then crushed into powder, or mixed with inorganic ceramic powder and then crushed for solid-solid mixing. Although this method is slightly inferior to the series of effects brought about by the aforementioned solid-liquid mixing, it still has advantages over the existing technology of first cracking and then sintering, that is, it will not reduce the sintering activity of the precursor, so that the prepared ceramic material has higher strength and density.

[0055] In some embodiments, the inorganic ceramic powder and the precursor solution are uniformly dispersed in a solvent to obtain a mixed solution, comprising:

[0056] The precursor solution is dissolved in the solvent, and ultrasonic stirring is performed for 10-15 minutes. The inorganic ceramic powder is added, and ultrasonic stirring is continued for 20-30 minutes to obtain the mixed solution.

[0057] In some of the embodiments, the protective atmosphere includes one or more of argon, nitrogen, ammonia, and hydrogen; the sintering methods include pressure sintering and pressureless sintering, and pressure sintering includes hot pressing sintering, gas pressure sintering, hot isostatic pressing sintering, spark plasma sintering, and high pressure sintering; the forming method of the green billet before pressureless sintering includes cold pressing and cold isostatic pressing.

[0058] Specifically, when the pressure sintering method is adopted, the mixed powder is sintered at low temperature under a protective atmosphere to obtain a low-temperature sintered dense bulk ceramic material including:

[0059] Place the mixed powder in a mold and sinter it under a protective atmosphere. Start pressurizing the mold at 800-1000℃ with a pressure of 40-80MPa. When the highest sintering temperature is reached, keep it warm for 2-120 minutes, release the pressure and cool it to room temperature.

[0060] When the sintering method is spark plasma sintering, the heating rate is 50-150°C / min, the sintering temperature is 1500-1700°C, the applied pressure is 40-50MPa, and the holding time is 3-10min.

[0061] Among them, when the sintering method is hot pressing sintering, the heating rate is 5-30°C / min, the sintering temperature is 1500-1700°C, the axial pressure is 50-60MPa, and the holding time is 30-120min.

[0062] Experiments have shown that better technical effects can be achieved under the above conditions.

[0063] The embodiment of the present invention also provides a low-temperature sintered dense bulk ceramic material, which is prepared based on the above-mentioned preparation method of the low-temperature sintered dense bulk ceramic material. The ceramic material of this embodiment consists of two parts, namely, a precursor-derived ceramic phase and an original inorganic ceramic phase. The so-called original inorganic ceramic phase is obtained after sintering the inorganic ceramic powder, and the derived ceramic phase is obtained by cracking the precursor at the sintering temperature. The precursor-derived ceramic phase uniformly covers and fills the surface and gaps of the inorganic ceramic phase.

[0064] The present invention will be further described below by means of specific examples.

[0065] Example 1

[0066] like Figure 1 The process shown in the embodiment is a method for preparing a dense SiBCN block, including the preparation of an organic-inorganic mixed powder and the sintering of a dense SiBCN block. The specific steps are as follows:

[0067] (1) Preparation of organic-inorganic mixed powders:

[0068] First, 3 g of polyborosilazane liquid and 7 g of amorphous SiBCN powder prepared by mechanical alloying were weighed respectively; secondly, polyborosilazane was dissolved in 150 mL of acetone solution and ultrasonically stirred for 10 min (120 W, 300 r / min); then, amorphous SiBCN powder was slowly added and ultrasonic stirring was continued for 20 min; the organic-inorganic mixed solution was transferred to a magnetic stirrer and the acetone solvent was evaporated (55°C) to a paste; finally, the obtained paste-like organic-inorganic mixed precursor was transferred to a vacuum drying oven, first dried at 80°C for 4 h to fully remove the acetone solvent, and then heated to 170°C for vacuum curing for 4 h; the organic-inorganic mixed powder was taken out and ground through a 200-mesh sieve to obtain an organic-inorganic mixed powder.

[0069] (2) Preparation of dense SiBCN blocks:

[0070] Weigh 8g of the organic-inorganic mixed powder prepared in step (1), place it in a graphite mold with an inner diameter of 30mm, and sinter it under nitrogen protection by hot pressing, with a heating rate of 20℃ / min, a sintering temperature of 1700℃, an axial pressure of 60MPa, and keep it warm for 1h. At high temperature, the organic polyborosilazane is cracked to generate amorphous SiBCN, and the reorganization of the amorphous SiBCN network structure provides a driving force for the movement of the amorphous SiBCN particles prepared by mechanical alloying, so that the powder produced by mechanical alloying can be sintered and densified at low temperature to obtain the corresponding dense block.

[0071] Comparative Example

[0072] The difference from Example 1 is that no precursor solution / powder is added, and the inorganic ceramic powder is directly hot-pressed and sintered, with a heating rate of 20° C. / min, a sintering temperature of 1800° C., an axial pressure of 60 MPa, and a heat preservation time of 1 h.

[0073] Figure 2 The microscopic morphology of the bulk ceramic fracture after sintering the pure inorganic ceramic powder and the organic-inorganic mixed powder of the comparative example and Example 1, wherein: Figure 2 (a) is the microscopic morphology of the bulk ceramic fracture obtained by sintering pure inorganic ceramic powder. Figure 2 (b) is the microscopic morphology of the bulk ceramic fracture obtained by sintering the organic-inorganic mixed powder. It can be seen that Figure 2 The ceramic material of (b) is more dense. It can be seen that the ceramic material prepared by Example 1 of the present invention has a higher density.

[0074] In addition, the bulk density of the dense block prepared by the comparative example (SiBCN powder produced by pure inorganic method without introducing precursor, using hot pressing sintering process, nitrogen atmosphere, 1800℃, 60MPa, heat preservation for 1h) is only 1.98g / cm 3In Example 1, after 30 wt% of polyborosilazane was introduced into the inorganic SiBCN powder, the bulk density of the block after sintering at 1700°C reached 2.37 g / cm 3 ; The bending strength is increased from 68MPa to 185MPa. Generally speaking, for SiBCN blocks, the higher the density of blocks with the same components, the more beneficial it is to its anti-oxidation. Therefore, the introduction of the precursor here is also beneficial to improving the density and bending performance of the SiBCN block.

[0075] Example 2

[0076] This embodiment provides a method for preparing a dense SiBCN block, including the preparation of an organic-inorganic mixed powder and the sintering of a dense SiBCN block, and the specific steps are as follows:

[0077] (1) Preparation of organic-inorganic mixed powders:

[0078] Weigh 20g of polyborosilazane precursor and place it in an alumina ark. Under the protection of nitrogen atmosphere, solidify it at 170℃ for 4h, cool it, take it out, crush it, grind it and sieve it. Weigh 3g of the solidified, crushed and ground polyborosilazane powder and 7g of amorphous SiBCN powder prepared by mechanical alloying respectively; place them in a high-energy ball mill, ball mill them at 400r / min for 30min, and pass through a 200-mesh sieve to obtain an organic-inorganic mixed powder.

[0079] (2) Preparation of dense SiBCN blocks:

[0080] Weigh 3.5g of the organic-inorganic mixed powder prepared in step (1), place it in a graphite mold with an inner diameter of 20mm, and sinter it under nitrogen protection by spark plasma, with a heating rate of 100℃ / min, a sintering temperature of 1700℃, an axial pressure of 50MPa, and keep warm for 5min. At high temperature, the organic polyborosilazane is cracked to generate amorphous SiBCN, and the reorganization of these amorphous SiBCN network structures provides a driving force for the movement of amorphous SiBCN particles prepared by mechanical alloying, so that the powder produced by mechanical alloying can be sintered and densified at low temperature to obtain a corresponding dense block.

[0081] Example 3

[0082] This embodiment provides a method for preparing a dense SiBCN block, including the preparation of an organic-inorganic mixed powder and the sintering of a dense SiBCN block, and the specific steps are as follows:

[0083] (1) Preparation of organic-inorganic mixed powders:

[0084] Weigh 16g of polysilazane precursor and place it in an alumina ark. Under nitrogen atmosphere, cure at 150℃ for 4h, cool, take out, crush, grind and sieve. Weigh 4g of the cured, crushed and ground polysilazane powder and 6g of amorphous SiBCN powder prepared by mechanical alloying respectively; place them in a high-energy ball mill, ball mill at 400r / min for 30min, and pass through a 200-mesh sieve to obtain an organic-inorganic mixed powder.

[0085] (2) Preparation of dense SiBCN blocks:

[0086] Weigh 3.5g of the organic-inorganic mixed powder obtained in step (1), place it in a quartz glass sleeve with an inner diameter of 15mm, and sinter it by hot isostatic pressing under nitrogen protection. The heating rate during sintering is 5℃ / min, the sintering temperature is 1600℃, and the applied pressure is 40MPa. At high temperature, the organic polyborosilazane is cracked to generate amorphous SiBCN. The reorganization of these amorphous SiBCN network structures provides a driving force for the movement of amorphous SiBCN particles prepared by mechanical alloying, so that the powder produced by mechanical alloying can be sintered and densified at low temperature to obtain a corresponding dense block.

[0087] Example 4

[0088] The difference between this embodiment and embodiment 3 is that during hot isostatic pressing for sintering, the heating rate is 5° C. / min, the sintering temperature is 1600° C., and the applied pressure is 40 MPa.

[0089] Example 5

[0090] This embodiment provides a method for preparing a dense BN block, including the preparation of an organic-inorganic composite powder and the sintering of a dense BN block, and the specific steps are as follows:

[0091] (1) Preparation of organic-inorganic mixed powders:

[0092] Weigh 20g of polyborazine precursor and place it in an alumina ark. Under nitrogen atmosphere, solidify it at 220℃ for 4h, cool it, take it out, crush it, grind it and sieve it. Weigh 3g of the solidified, crushed and ground polyborazine powder and 7g of inorganic BN powder respectively; place them in a ball mill, ball mill them at 400r / min for 10h, and pass them through a 200-mesh sieve to obtain an organic-inorganic mixed powder.

[0093] (2) Preparation of dense BN blocks:

[0094] Weigh 3.5 g of the organic-inorganic mixed powder obtained in step (1), place it in a graphite mold with an inner diameter of 20 mm, and sinter it under nitrogen protection by spark plasma, with a heating rate of 100°C / min, a sintering temperature of 1700°C, an axial pressure of 50 MPa, and keep warm for 5 minutes. At high temperature, organic polyborazine is cracked to generate amorphous BN, and the reorganization of these amorphous BN network structures provides a driving force for the movement of inorganic BN particles, so that it can achieve low-temperature sintering densification to obtain the corresponding dense block.

[0095] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a low-temperature sintered dense bulk ceramic material, characterized in that: include: Inorganic ceramic powder and precursor solution are used as raw materials, and mixed and dispersed to obtain a mixed powder, wherein the weight percentage of the precursor solution in the mixed powder is 10-40wt%; The mixed powder is sintered at low temperature under a protective atmosphere to obtain a low-temperature sintered dense bulk ceramic material; Wherein, when the inorganic ceramic powder and the precursor solution are mixed and dispersed as raw materials to obtain the mixed powder, the method comprises: uniformly dispersing the inorganic ceramic powder and the precursor solution in acetone to obtain a mixed solution; heating and stirring the mixed solution to evaporate the acetone until the mixed solution becomes a paste; The paste-like mixed solution is first dried at 80-90° C. for 4-5 hours to fully remove the acetone, then heated to 170-180° C., solidified for 4-6 hours, and crushed to obtain the mixed powder; The precursor solution includes one or more of polysilane, polysilazane, polycarbosilane, polysiloxane, polyborazane and polyborosilazane.

2. The method for preparing a low-temperature sintered dense bulk ceramic material according to claim 1, characterized in that: The step of heating and stirring the mixed solution to evaporate the acetone until the mixed solution becomes a paste comprises: The mixed solution was placed on a magnetic stirrer, and the acetone was evaporated at 50-55° C. until the mixed solution became a paste.

3. The method for preparing a low-temperature sintered dense bulk ceramic material according to claim 1, characterized in that: The inorganic ceramic powder and the precursor solution are uniformly dispersed in acetone to obtain a mixed solution, comprising: The precursor solution is dissolved in the acetone, and ultrasonic stirring is performed for 10-15 minutes. The inorganic ceramic powder is added, and ultrasonic stirring is continued for 20-30 minutes to obtain the mixed solution.

4. The method for preparing a low temperature sintered dense bulk ceramic material according to claim 1, characterized in that: The low-temperature sintering includes spark plasma sintering. The heating rate during the spark plasma sintering is 50-150° C. / min, the sintering temperature is 1500-1700° C., the applied pressure is 40-50 MPa, and the holding time is 3-10 min.

5. The method for preparing a low temperature sintered dense bulk ceramic material according to claim 1, characterized in that: The low-temperature sintering includes hot pressing sintering, and the heating rate during the hot pressing sintering is 5-30°C / min, the sintering temperature is 1500-1700°C, the axial pressure is 50-60MPa, and the insulation time is 30-120min.

6. A low-temperature sintered dense bulk ceramic material, characterized in that: The method for preparing a low-temperature sintered dense bulk ceramic material is based on any one of claims 1 to 5.

Citation Information

Patent Citations

  • Low-temperature sintering method of ultra-high-temperature ceramic

    CN107879743A

  • Preparation method and densification process of ultrahigh-temperature multiphase ceramic powder

    CN111732437A